Enhancing the correctness of BPMN models - Correia, A.; Brito e Abreu, F. (Sustainable business: Concepts, methodologies, tools, and applications, 2020)
While some of the OMG's metamodels include a formal specification of well-formedness rules, using OCL, the BPMN metamodel specification only includes those rules in natural language. Although several BPMN tools claim to support, at least partly, the OMG's BPMN specification, we found that the mainstream of BPMN tools do not enforce most of the prescribed BPMN rules. Furthermore, the verification of BPMN process models publicly available showed that a relevant percentage of those BPMN process models fail in complying with the well-formedness rules of the BPMN specification. The enforcement of process model's correctness is relevant for the sake of better quality of process modeling and to attain models amenable of being enacted. In this chapter we propose supplement the BPMN metamodel with well-formedness rules expressed as OCL invariants in order to enforce BPMN models' correctness.